PHILOSOPHICAL VIEW OF THE CAUSES OF PERSONAL ALIENATION - Abdurakhmanov Zaribjon Mansurovich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article examines the origins of alienation and the philosophical aspects of this process. The article analyzes changes in a person's self-awareness, place in society, and disruptions in social relations. The social, cultural, and economic factors of alienation are also examined, and how this process relates to personal experiences and psychological states is explained.